Pharmacokinetic/pharmacodynamics-optimized antimicrobial therapy in patients with hospital-acquired pneumonia/ventilator-associated pneumonia - Sulaiman, Helmi; Abdul Aziz, Mohd. Hafiz; Roberts, Jason A. (2017)
Hospital-acquired pneumonia and ventilator-associated pneumonia continue to cause significant morbidity and mortality. With increasing rates of antimicrobial resistance, the importance of optimizing antibiotic treatment is key to maximize treatment outcomes. This is especially important in critically ill patients in intensive care units, in whom the infection is usually caused by less susceptible organisms. In addition, the marked physiological changes that can occur in these patients can cause serious changes in antibiotic pharmacokinetics which in turn alter the attainment of therapeutic drug exposures. This article reviews the various aspects of the pharmacokinetic changes that can occur in the critically ill patients, the barriers to achieving therapeutic drug exposures in pneumonia for systemically delivered antibiotics, the optimization for commonly used antibiotics in hospital- and ventilator-associated pneumonia, the agents that should be avoided in the treatment regimen, as well as the use of adjunctive therapy in the form of nebulized antibiotics.